Integration of Circular Economy and Zero Waste in the Transformation of Pineapple MSMEs in Kediri towards a Sustainable Halal Value Chain - Nur Azizah; Tri Yulia Rachmawati; Guslina Ekasanti (Universitas Islam Darul 'ulum Lamongan, 2026)
This study aims to analyse the integration of the circular economy and zero-waste principles in the transformation of pineapple-based micro, small, and medium enterprises (MSMEs) in Kediri towards a sustainable halal value chain. The research addresses the persistent challenges associated with the limited implementation of sustainable waste management practices and the inadequate integration of halal values across the entire MSME production chain. A qualitative approach employing an exploratory case study design was adopted, with data collected through in-depth interviews, field observations, and documentation analysis. The findings reveal that the implementation of circular economy principles among pineapple MSMEs remains partial and fragmented, primarily reflected in the utilisation of organic waste as animal feed and compost. Meanwhile, the zero-waste concept has not yet been systematically implemented due to constraints related to knowledge, technology, and institutional support. From the perspective of the halal value chain, most business actors continue to focus predominantly on the halal status of the final product, without comprehensively integrating halal principles throughout the production, processing, and distribution stages of the value chain. This study proposes an integrative model that links the circular economy, zero waste, and halal value chain within locally based MSMEs as a strategic approach to strengthening environmental sustainability, enhancing production efficiency, and improving global business competitiveness.